Screening of nanocomposite scaffolds arrays using superhydrophobic-wettable micropatterns - Leite, Álvaro J. (2017)
Platforms containing multiple arrays for high-throughput screening are demanded in the development of biomaterial libraries. Here, an array platform for the combinatorial analysis of cellular interactions and 3D porous biomaterials is described. Using a novel method based on computer-aided manufacturing, wettable regions are printed on superhydrophobic surfaces, generating isolated spots. This freestanding benchtop array is used as a tool to deposit naturally derived polymers, chitosan and hyaluronic acid, with bioactive glass nanoparticles (BGNPs) to obtain a scaffold matrix. The effect of fibronectin adsorption on the scaffolds is also tested. The biomimetic nanocomposite scaffolds are shown to be osteoconductive, non-cytotoxic, promote cell adhesion, and regulate osteogenic commitment. The method proves to be suitable for screening of biomaterials in 3D cell cultures as it can recreate a multitude of combinations on a single platform and identify the optimal composition that drives to desired cell responses. The platforms are fully compatible with commercially routine cell culture labware and established characterization methods, allowing for a standard control and easy adaptability to the cell culture environment. This study shows the value of 3D structured array platforms to decode the combinatorial interactions at play in cell microenvironments.